2006
DOI: 10.1002/adma.200601830
|View full text |Cite
|
Sign up to set email alerts
|

RuO2 Nanowires and RuO2/TiO2 Core/Shell Nanowires: From Synthesis to Mechanical, Optical, Electrical, and Photoconductive Properties

Abstract: Functional 1D metal oxides have attracted much attention because of their unique applications in electronic, optoelectronic, and spintronic devices.[1] For semiconducting oxide nanowires (NWs) (e.g., ZnO, In 2 O 3 , and SnO 2 NWs), field-effect transistors and light-emitting diodes have been demonstrated. [2] Metallic oxide nanoscale materials, such as nanoscale RuO 2 , can be good candidates as interconnects in electronic applications.[3] RuO 2 nanomaterials have been produced by chemical vapor deposition (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 59 publications
6
82
2
Order By: Relevance
“…Similar behavior was studied by our group and other groups. 12,13,23,36 We have observed in previous fundamental studies 23 We carried out DFT studies to understand the electronic band structure of the heterojunction nanocomposites which strongly affects the photocatalytic water splitting performance. In Figure 5A, we show the density of states (DOS) of the full-relaxed (3x6)…”
Section: Sem Images Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behavior was studied by our group and other groups. 12,13,23,36 We have observed in previous fundamental studies 23 We carried out DFT studies to understand the electronic band structure of the heterojunction nanocomposites which strongly affects the photocatalytic water splitting performance. In Figure 5A, we show the density of states (DOS) of the full-relaxed (3x6)…”
Section: Sem Images Inmentioning
confidence: 99%
“…6,5 Coupling rutile TiO2 with RuO2 has been widely studied in numerous catalytic reactions due to their lattice matching and strong metal-support interaction. [12][13][14][15][16][17] claimed that RuO2/rutile-TiO2 catalyst exhibited high catalytic activity and thermal stability toward HCl oxidation to Cl2 due to highly dispersed, ultrafine RuO2 crystallites, approximately a single unit-cell thickness, that cover the surface of TiO2 primary particle with strong interaction between RuO2 and TiO2. Xiang et al 15 demonstrated that the redistribution or spreading of RuO2 occurred from a spherical shape (~ sub 2 nm) to epitaxial island layers along the TiO2 surfaces during the chlorination reaction, forming a unique heterostructure at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, RuO 2 /TiO 2 core-shell nanowires were prepared by first growing RuO 2 nanowires by reactive sputtering, followed by sputtering of the TiO 2 layer onto the surface of the RuO 2 nanowire. [78] 1.4 CHARACTERISATION…”
Section: Preparation Of Nanoionic Materialsmentioning
confidence: 99%
“…The photocatalytic degradation of various toxic compounds in aqueous solutions using fine titanium oxide particles has been studied by many researchers (Kudo and Kudo 2006;Tran and Nosaka 2006;Chueh and Hsieh 2007;Ghicov and Schmidt 2007;Hu and Dai 2007;Macak and Zlamal 2007;Meng and Hao 2007;Wang and Ma 2007;Weiher and Beesley 2007;Yu and Yu 2007). However, to avoid the filtration and suspension of small particle photocatalysts, the composite supports containing titania with silica, alumina or other metal oxides have been proposed (Alexeev and Chin 2005;Chu and Inoue 2005;Feng and Miedaner 2005;Yang and Zeng 2005;Li and Wu 2006;Zhang and Zhou 2006).…”
Section: Introductionmentioning
confidence: 97%